2014
DOI: 10.1111/sltb.12150
|View full text |Cite
|
Sign up to set email alerts
|

Seemingly Harmless Racial Communications Are Not So Harmless: Racial Microaggressions Lead to Suicidal Ideation by Way of Depression Symptoms

Abstract: Racial microaggressions, a contemporary form of subtle discrimination that occurs in everyday interactions, are associated with a variety of negative mental health outcomes. Research has not extended the connection between racial microaggressions and negative mental health to include suicide risk. Given the well-known association between negative mental health outcomes and suicide risk, the current study examined whether racial microaggressions predicted suicidal ideation through depression symptoms among 405 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(83 citation statements)
references
References 38 publications
6
76
1
Order By: Relevance
“…There is compelling evidence demonstrating a link between racial/ethnic discrimination and depressive symptoms (Pascoe and Richman 2009), with research demonstrating depressive symptoms may explain the relation between racial/ethnic discrimination and risk for suicidal behavior (O'Keefe et al 2015;Walker et al 2014). Specifically, one study found perceived racism (i.e., perceptions of racism across interpersonal and institutional levels) was associated with increases in suicidal ideation among African American adults to the degree that it was associated with increases in depressive symptoms (Walker et al 2014).…”
Section: Racial/ethnic Discrimination As a Race-based Traumatic Stressormentioning
confidence: 99%
“…There is compelling evidence demonstrating a link between racial/ethnic discrimination and depressive symptoms (Pascoe and Richman 2009), with research demonstrating depressive symptoms may explain the relation between racial/ethnic discrimination and risk for suicidal behavior (O'Keefe et al 2015;Walker et al 2014). Specifically, one study found perceived racism (i.e., perceptions of racism across interpersonal and institutional levels) was associated with increases in suicidal ideation among African American adults to the degree that it was associated with increases in depressive symptoms (Walker et al 2014).…”
Section: Racial/ethnic Discrimination As a Race-based Traumatic Stressormentioning
confidence: 99%
“…18 The concept was originally applied to the well-being of the African-American community and has since become more broadly attributed to the effect of these actions on additional marginalized groups, including sexual minorities. 18 , 19 In a 2016 American Psychological Association article, Spengler et al 20 wrote, “The stigma and prejudice [marginalized groups] regularly encounter is hypothesized to lead to their significantly increased risk for developing mental health disorders.” The collective literature on microaggressions and health care supports this theory, pointing broadly toward unfavorable health outcomes, including greater risk of depression and suicide ideation among patients, 19 diminished treatment effectiveness, and decreased utilization. 20 Provider misuse of gender pronouns and preferred name and lack of clinical capacity to provide inclusive care should be considered microaggressions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of young adults of color, O’Keefe and colleagues found an association between racial microaggressions and suicide-related outcomes mediated by depressive symptoms. 32 To our knowledge, the mechanism by which racial microaggressions and gender minority status interact to produce changes in sexual risk behavior is unclear for trans*female youth. Although the present study attempts to analyze the role of racial discrimination in risk behavior, there is a need for using measures that are sensitive and relevant to the discrimination experiences of diverse populations, such as racial/ethnic minority trans*female youth, to rigorously inform targeted HIV intervention efforts.…”
Section: Discussionmentioning
confidence: 99%